PANJANG DAN LEBAR CORPUS MANDIBULA TIKUS WISTAR SETELAH PEMBERIAN SUSU KAMBING ETAWA SELAMA PERIODE POST NATAL - Lestari, Sri; Azza, Ade; Adriatmoko, Winny (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Optimum mandible growth needs sufficient nutrition like protein and mineral in a large amount. The main mineral for bone growth is calcium, wich largely contained in milk, including Etawa sheep milk that is very popular lately. The aim of this study was to observe the difference of length and width of corpus mandible of wistar rats after being administered with Etawa sheep milk during post natal period. This study was laboratory experiment, 12 baby wistars aged 21 days were divided into 2 groups, 6 wistar for control administered with standard food and breastfed their mother. Treatment group comprised of 6 baby wistarswere administered with Etawa sheep milk using sonde and also breastfed their mother. After 60 days old, they were killed and their mandibles were decapitated and cleaned from their soft tissue.It was subsequently conducted a measurement on the length and with of their corpus mandibles. The data were then tested using T-test methode. The data showed that the length and width of the corpus mandibles were increased through Etawasheep administration. T-test showed a significant difference in the length and width of the corpus mandibles between the wistars administered with standard food and the wistars administered with Etawa sheep milk